Analisis Komunikasi Non-Verbal di Line (Studi Kasus Hubungan Jarak Jauh pada Mahasiswa Fikom Untar) - Aura Diva Maria Br Simanjorang; Sisca Aulia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Nonverbal communication is often more powerful than verbal communication, as it can emphasize, strengthen, and even replace spoken messages. In the context of interpersonal relationships, communication. This study discusses the role of nonverbal communication in maintaining emotional closeness among Untar Faculty of Communication Sciences students in long-distance relationships, particularly through the LINE application. In the digital era, nonverbal expressions are no longer only manifested through physical gestures, but also through visual symbols such as stickers, emojis, message reply patterns, and audio features. This study aims to analyze the forms of nonverbal communication used by students in long-distance relationships and understand how these elements help maintain the quality of interpersonal relationships. This study uses Paul Ekman and Wallace Friesen's Kinesics theory, which includes five categories of nonverbal expression: emblem, illustrator, regulator, affect display, and adapter, as the basis for analysis. The research method used is a qualitative approach with in-depth interview techniques and source triangulation. The results show that stickers and emojis are the most dominant digital symbols for expressing emotions, clarifying messages, and reducing miscommunication. Additionally, features like voice notes, reply pauses, and